Effect of malaria on placental volume measured using three-dimensional ultrasound: a pilot study - Rijken Marcus J; Moroski William E; Kiricharoen Suporn; Karunkonkowit Noaeni; Stevenson Gordon; Ohuma Eric O; Noble J Alison; Kennedy Stephen H; McGready Rose; Papageorghiou Aris T; Nosten François H (Malaria Journal, 2012)
Abstract Background The presence of malaria parasites and histopathological changes in the placenta are associated with a reduction in birth weight, principally due to intrauterine growth restriction. The aim of this study was to examine the feasibility of studying early pregnancy placental volumes using three-dimensional (3D) ultrasound in a malaria endemic area, as a small volume in the second trimester may be an indicator of intra-uterine growth restriction and placental insufficiency. Methods Placenta volumes were acquired using a portable ultrasound machine and a 3D ultrasound transducer and estimated using the Virtual Organ Computer-aided AnaLysis (VOCAL) image analysis software package. Intra-observer reliability and limits of agreement of the placenta volume measurements were calculated. Polynomial regression models for the mean and standard deviation as a function of gestational age for the placental volumes of uninfected women were created and tested. Based on these equations each measurement was converted into a z -score. The z-scores of the placental volumes of malaria infected and uninfected women were then compared. Results Eighty-four women (uninfected = 65; infected = 19) with a posterior placenta delivered congenitally normal, live born, single babies. The mean placental volumes in the uninfected women were modeled to fit 5th, 10th, 50th, 90th and 95th centiles for 14-24 weeks' gestation. Most placenta volumes in the infected women were below the 50th centile for gestational age; most of those with Plasmodium falciparum were below the 10th centile. The 95% intra-observer limits of agreement for first and second measurements were ± 37.0 mL and ± 25.4 mL at 30 degrees and 15 degrees rotation respectively. Conclusion The new technique of 3D ultrasound volumetry of the placenta may be useful to improve our understanding of the pathophysiological constraints on foetal growth caused by malaria infection in early pregnancy.